Volume and Surface Area Shrinkages of Some Hybrid Corn Varieties - Junaedi Muhidong; Akbal Akbal (Hasanuddin University, 2016)
Hybrid corn has been popular to Indonesian corn farmers in recent years. Nonetheless, physical properties of hybrid corn kernels, including their shrinkage behavior, are rarely investigated to support a more efficient post harvest handling. This research was designed to explore the shrinkage behavior of the kernels of five hybrid corn varieties (NK77, DK77, Pioneer, Makmur, and Bisi-2). The study was conducted in the Processing Laboratory of Agricultural Engineering Department, Hasanuddin University, Indonesia, in 2011. Five relatively homogenous kernels from each variety were selected and dried under a temperature of about 47oC with drying air velocity of 1.0 m/s, using a tray dryer, Model EHTD- 300 Eunha Fluid Science. A caliper with an accuracy of 0.05 mm was used to measure the orthogonal dimensions of the kernels. Such dimensions were transformed into volume and surface area ratios. The behaviours of these ratios as a function of moisture contents, called shrinkage behaviors, were fitted to Rahman, Bala and Wood, Corrêa et al. and polynomial quadratic models. The results strongly suggested that there was no single model which was consistently more superior in estimating the shrinkage behaviors of both volume and surface area of the hybrid corn varieties of NK22, DK77, Pioneer, Makmur, and Bisi-2 than the other models. However, compared with the other two models, the Bala and Wood and the polynomial quadratic models consistently provided high R2 values.